Efficient apoptosis requires feedback amplification of upstream apoptotic signals by effector caspase-3 or -7 - McComb, Scott (Sci Adv, 2019)
Apoptosis is a complex multi-step process driven by caspase-dependent proteolytic cleavage cascades. Dysregulation of apoptosis promotes tumorigenesis and limits the efficacy of chemotherapy. To assess the complex interactions among caspases during apoptosis, we disrupted caspase-8, -9, -3, -7, or -6 and combinations thereof, using CRISPR-based genome editing in living human leukemia cells. While loss of apical initiator caspase-8 or -9 partially blocked extrinsic or intrinsic apoptosis, respectively, only combined loss of caspase-3 and -7 fully inhibited both apoptotic pathways, with no discernible effect of caspase-6 deficiency alone or in combination. Caspase-3/7 double knockout cells exhibited almost complete inhibition of caspase-8 or -9 activation. Furthermore, deletion of caspase-3 and -7 decreased mitochondrial depolarization and cytochrome c release upon apoptosis activation. Thus, activation of effector caspase-3 or -7 sets off explosive feedback amplification of upstream apoptotic events, which is a key feature of apoptotic signaling essential for efficient apoptotic cell death.